2021
DOI: 10.1021/acsami.0c15324
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Characteristics of Electrospun Gas Diffusion Layers with Custom Pore Structures for Polymer Electrolyte Membrane Fuel Cells

Abstract: Electrospinning has been demonstrated to be a versatile technique for producing hydrophobic gas diffusion layers (GDLs) with customized pore structures for the enhanced performance of polymer electrolyte membrane (PEM) fuel cells. However, the degradation characteristics of custom hydrophobic electrospun GDLs (eGDLs) have not yet been explored. Here, for the first time, we investigate the degradation characteristics of custom hydrophobic eGDLs via an ex situ accelerated degradation protocol using H2O2. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…However, this part of the signal was significantly increased in the GDL modified with HFTS, which was caused by the introduction of hydroxyl groups during nitrification . A binding energy of >290 eV is the signal belonging to C–F Figure b shows the fluorine signals of carbon paper modified with PTFE and HFTS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this part of the signal was significantly increased in the GDL modified with HFTS, which was caused by the introduction of hydroxyl groups during nitrification . A binding energy of >290 eV is the signal belonging to C–F Figure b shows the fluorine signals of carbon paper modified with PTFE and HFTS.…”
Section: Resultsmentioning
confidence: 99%
“…29 A binding energy of >290 eV is the signal belonging to C−F. 15 Figure 2b shows the fluorine signals of carbon paper modified with PTFE and HFTS. Only one fluorine signal appears in both samples, which indicates that no other impurities are formed in this liquid phase reaction.…”
Section: Properties and Performance Of Gdlmentioning
confidence: 99%
See 1 more Smart Citation
“…However, electrochemical and polarisation curves were not performed and as such the full conclusion of the capability of the e-GDL in a PEMFC has yet to be confirmed. Certain challenges need to be overcome to improve e-GDL durability as Balakrishnan et al [26] reported a notable drop in contact angle (from 136 • to 44 • ) after accelerated stress tests in hydrogen peroxide due to a degradation of the fluorinated monolayers. Polarisation curves indicated that the degraded electrospun GDL suffered higher levels of liquid water accumulation and mass transport losses than the pristine with a significant potential drop voltage following the 0.5 A cm − 2 .…”
Section: Electrospun Mpsmentioning
confidence: 99%
“…Using highly oriented sulfonated PI nanofibers, Tamura and Kawakami produced proton exchange membranes for fuel cells with high chemical and mechanical stability as well as high proton conductivity parallel to the nanofibers [ 239 ]. Electrospun nanofibers mats with pore size gradients were suggested by Balakrishan et al for polymer-electrolyte membrane fuel cells [ 240 ], who also studied degradation of such electrospun gas diffusion layers [ 241 ], while Kallem et al highlight some possible strategies for nanofiber-based proton exchange membranes with aligned nanofiber mats [ 242 ].…”
Section: Fuel Cellsmentioning
confidence: 99%